Procedural (In)Justice as Inclusivity and Marginalization: Evidence from a Longitudinal Sample of Mexican-American Adolescents. (February 2022) - Thompson, Andrew J.; Wilson, Theodore
Objectives: Treatment by law enforcement officers, as representatives of the state that interact with individual citizens, may signal to individuals their political and social inclusion within society. Hispanics, as the largest minority group in the country that oftentimes must navigate two cultural identities, may be especially sensitive to the treatment of police. We test the group engagement model's implication that procedural justice—or lack thereof—may promote or hinder attachment to the United States and/or Mexico among Latino/a adolescents and young adults. Methods: Using a fixed effects panel design with a subsample of Mexican Americans from the Pathways to Desistance Study, we examine whether changes in subjective procedural justice evaluations of the police are related to changes in National identification. Results: Changes in procedural justice perceptions are significantly related to changes in Mexican identification, whereas procedural justice is not related to changes in Anglo identification. Although, consistent with segmented assimilation theory, the relationships between changes in procedural justice and Mexican/Anglo identification may be stronger among participants born in the United States. Conclusions: The findings are generally consistent with the group engagement model of procedural justice and suggest procedural injustice may alienate Hispanics.